Effect of Organic Manures on Phosphorus Use Efficiency in Summer Rice in Acidic Soil of Northern Part of West Bengal - Roy, Subrata; Banik, G. C.; Pradhan, Pratistha (International Journal of Bio-resource and Stress Management, 2025)
A field experiment was conducted in boro (summer) seasons during December to May, 2021–22 and 2022–23 at Central Research Farm of Uttar Banga Krishi Viswavidyalaya, Pundibari, Cooch Behar, West Bengal, India, in acidic soil (pH 5.10) of the terai region of West Bengal to assess the effect of replacing phosphorus (P) fertilizer application by farm yard manure (FYM) and vermicompost (VC) on P uptake and use efficiency by summer rice. The soil of the study area was sandy loam, medium in available P (16.48 kg ha-1) content and deficient in available N (126.68 kg ha-1). The experiment was laid out in a randomized complete block design with eleven treatment combinations including four P doses i.e., 25%, 50%, 75% and 100% of the recommended dose, the rest of which were supplemented by either FYM or VC. Significantly higher P uptake at different growth stages was noticed with the increasing fertilizer P application. Combined use of 25% P and 75% vermicompost was most effective for grain yield (5.70 t ha-1), harvest index (HI) (42.80%) and agronomic P use efficiency (APUE) (15.25 kg kg-1). Increasing fertilizer P dose to 75% and 100% with or without organic manures was not found effective in increasing yield and P use efficiency, while was also effective in uptake of P and apparent P recovery.